Factors that contributing in influencing mobile phone usage among university students - Munusamy, Kalaivani; Ahmad Ghazali, Akmar Hayati (Human Resource Management Academic Research Society, 2023)
Mobile phone technology has gradually become integrated into the higher education experience and nearly every member of the university community uses or owns a mobile phone to connect with others. According to past research there is a strong association between gender, self-esteem, social anxiety and mobile phone use. However, there has very few researches on self-esteem, and social anxiety towards mobile phone usage. Regardless of the distance between people, mobile phones allow them to interact and integrate on a regular basis. Even though these benefits are present, mobile phone has been identified as global problem, particularly among teenagers. Therefore, this study was examine the factors that influence on mobile phone usage. The purpose of this study was to determine the impact of gender, self-esteem and social anxiety towards mobile phone addiction among public university students in Klang Valley. In this study, a survey method was used. There were 400 teenagers from four public universities took part in this survey. The findings conclude that gender differences, self-esteem and social anxiety not influencing on the mobile phone usage among teenagers. Mobile phones are an inevitable part of modern life and it would be an indispensable tool in our society. However, over use of mobile phone has resulted in the problem of mobile addiction. Hence, need to identify main causes that influencing mobile phone use among teenagers before it’s affect the student’s academic performance and their productivity.